The roles of clinical social worker in facing rumors regards vaccines coronavirus (Covid 19) - Abu Alola, Turki Hassan (Journal of Humanities & Social Sciences, 2022)
The current research aims to identify the roles of the medical social worker in facing rumors directed against COVID-19 vaccines. The descriptive research relied on the social survey method by complete census of all female and male social workers in Makkah hospitals, whose numbered (94) individuals. Data were collected by the questionnaire from (90) individuals. The results showed the vast majority of respondents indicated that social media such as WhatsApp and Twitter have clearly contributed to spreading these rumors. The most common forms of rumors circulating about vaccines are: (blood clots and sterility). The results also showed that the most important roles of the medical social worker are educating customers about the importance of COVID-19 vaccines, correct misconceptions and ideas related to vaccines. The results also showed that the most important skills used by the social worker were forming a professional relationship, giving them the necessary awareness to confront rumors. The research recommended that Clinical social workers should pay attention to conducting awareness to educate patients, their families, and the local community about the danger of rumors. Moreover, Clinical social workers should motivate people to take vaccinations to achieve health security in the community. Also, developing the knowledge and skills of social workers about the vaccinations and the methods of confronting rumors and paying attention to the media in spreading and educating citizens about the importance of taking vaccinations.